2005
DOI: 10.1128/iai.73.2.1221-1225.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New hmwA Alleles from Nontypeable Haemophilus influenzae

Abstract: High-molecular-weight proteins of Haemophilus influenzae mediate attachment to epithelial cells. Previous reports describe several allelic versions of hmwA genes that have different adherence properties. Here we report three new alleles of hmwA (hmwA from strain AAr96, hmwA from strain AAr105, and hmwA from strain G822), demonstrating the high degree of DNA variation of these genes among different strains.Nontypeable Haemophilus influenzae (NTHi), a gram-negative, nonencapsulated, human-specific microorganism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…In comparison with strain 12 sequences, both the hmw1A and hmw2A genes from strain 72 displayed high conservation at the 5Ј end of the gene and at the 3Ј end, while the middle portion exhibited considerable genetic diversity as a result of multiple point mutations, insertions, and deletions. These data confirmed that the middle portion of the hmwA genes diverges not only between the hmw1A and hmw2A genes from strain 12 but also among each hmw1A gene and among each hmw2A gene from different isolates (9).…”
Section: Vol 74 2006 Variation In H Influenzae Hmw Binding Domainssupporting
confidence: 73%
See 1 more Smart Citation
“…In comparison with strain 12 sequences, both the hmw1A and hmw2A genes from strain 72 displayed high conservation at the 5Ј end of the gene and at the 3Ј end, while the middle portion exhibited considerable genetic diversity as a result of multiple point mutations, insertions, and deletions. These data confirmed that the middle portion of the hmwA genes diverges not only between the hmw1A and hmw2A genes from strain 12 but also among each hmw1A gene and among each hmw2A gene from different isolates (9).…”
Section: Vol 74 2006 Variation In H Influenzae Hmw Binding Domainssupporting
confidence: 73%
“…On the other hand, sequence analysis of hmwA alleles from different isolates revealed a high level of polymorphism in the receptor binding regions (9). In this study, a PCR approach in conjunction with DNA sequencing was used to investigate the conservation and diversity of the HMW1 and HMW2 binding domain sequences among isolates.…”
mentioning
confidence: 99%
“…Several host and epidemiological factors play a role in otitis media pathogenesis, including genetic predisposition, preceding viral respiratory infections, attendance in day care centers, lack of breastfeeding, and young age (7,12,48,55). Recent data suggest that bacterial virulence factors also play a role in otitis media (40), such as lic2B, which is involved in lipooligosaccharide biosynthesis, and the hmw genes, which encode highmolecular-weight adhesins (17,46). These two genes were shown to be more prevalent in middle ear isolates than in throat strains from healthy children, suggesting their role in otitis media virulence.…”
mentioning
confidence: 99%
“…As might have been predicted, the opsonophagocytic activity of a given immune serum was in all instances as active or more active against the respective homologous strain than were any of the other immune sera (Table 2). However, despite the known variability in the predicted amino acid sequences of the HMW1/HMW2-like proteins from different nontypeable Haemophilus influenzae strains (9,18,23), the immune sera were frequently able to mediate opsonophagocytic killing of heterologous strains. As a case in point, the predicted amino acid sequences of the HMW1/HMW2-like proteins of strains 12 and 15 demonstrated between 65 and 81% sequence identity when the four sequences were aligned and compared (18,60).…”
Section: Discussionmentioning
confidence: 99%
“…At the extreme was nontypeable Haemophilus strain 14, a strain resistant to killing by all of the immune sera that we had prepared. While strain-tostrain variation in the amino acid sequences of the HMW1/ HMW2-like proteins undoubtedly accounts for some of the differences observed (9,18,23), other explanations also deserve consideration. The bacterial surface of nontypeable Haemophilus influenzae is known to be a very dynamic structure.…”
Section: Discussionmentioning
confidence: 99%